Synthesizing and Performance Testing of Zn Promoted Ni Catalyst With γ-Al2O3 Support in The Process of Hydrotreating Used Cooking Oil into Green Diesel - Kopli, Faizal Zul; Fadel Kurnia Artha; Ismeini, Ismeini; Erlinawati, Erlinawati; Ramandani, Adityas Agung; Efendi, Dimas Amirul Mukminin Nur (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2024)
Green diesel was a mixture of straight-chain and branched-chain alkanes, typically mostly 15 to 18 carbon atoms per molecule (C15 to C18) extracted from the hydrotreating process of vegetable oils. In this study, a catalyst of Nickel (Ni) promoted Zinc (Zn) supported by Alumina (Al2O3) was used. The catalyst was made by varying the use of and without the Zn promoter in the catalyst. Catalyst tested for Scanning Electron Microscope characterization. For the 60Ni/Al2O3 catalyst, the total area was 51,575.51 m2/gr, while for the 15Ni-45Zn/Al2O3 catalyst, the total area was 20.577,55 m2/gr. Furthermore, a performance test of the catalyst was also carried out using a green diesel reactor with a temperature of 400°C and a pressure of 20 bar, the percentage yield on the 60Ni/Al2O3 catalyst was 25.73% while the 30Ni-30Zn/Al2O3 catalyst was 23.60%. The 60Ni/Al2O3 catalyst has the following properties: physical properties such as density, viscosity, flash point, cetane number, and acid number of 765.17 ± 0.249 kg/m3, 3.55 ± 0.076 mm2/s, 60.73 ± 0.170°C, 88.10 ± 0.648 CN, and 0.33 ± 0.76 mgKOH/g, respectively. The 15Ni-45Zn/Al2O3 catalyst has the following properties: physical properties such as density of 766.77 ± 0.679 kg/m3, viscosity of 66.13 ± 0.249 mm2/s, flash point of 2.92 ± 0.011°C, cetane number of 82.33 ± 0.386, and acid number of 82.33 ± 0.386 mgKOH/g.